Helen Greiner : cofounder of the iRobot Corporation - Schulte, Mary, 1958- (Detroit, MI : KidHaven Press, 2009)
Traces the life of Helen Greiner, the cofounder of the iRobot Corporation.
Creator of everyday robots -- A fascination with robots -- Hard-working robots -- A robot for every home -- Encouraging women in technology.
Includes bibliographical references and index.
Keywords: Greiner, Helen, -- 1967- -- Juvenile literature; Greiner, Helen, -- 1967-; Mechanical engineers -- United States -- Biography -- Juvenile literature; Inventors -- United States -- Biography -- Juvenile literature; Mechanical engineers -- United States -- Biography; Inventors -- United States -- Biography